Influence of early-life stress on hippocampal synaptic and network properties - Rozov, Andrei; Fedulina, Anastasia; Krut’, Viktoriya; Sokolov, Rostislav; Sulimova, Arina; Jappy, David (Frontiers in Neural Circuits, 2024)
According to the World Health Organization, the number of people suffering from depressive disorders worldwide is approaching 350 million. The consequences of depressive disorders include considerable worsening of the quality of life, which frequently leads to social isolation. One of the key factors which may cause depression in adulthood is early life stress, in particular, insufficient maternal care during infancy. Studies performed with children raised in orphanages have shown that long-term complete absence of maternal care (chronic early life stress) leads to vulnerability to emotional disorders, including depression, in adulthood. All of the above dictates the need for a deep understanding of the mechanisms of the pathogenicity of stress in neurogenesis. Therefore, the consequences of stress experienced in the early stages of development are actively studied in animal models. A large body of evidence has accumulated indicating stress-induced changes in gene expression and behavioral disorders in adulthood. However, the connection between the molecular biology of neurons and complex behavior runs through the synaptic connections linking these neurons into complex neural networks. In turn, coordinated activity in neuronal ensembles, achieved by a balance of synaptic excitation and inhibition, is the basis of complex behavior. Unfortunately, the effect of stress on synaptic interactions of neurons remains poorly understood.